Impact of Forest Landscape Restoration (FLR) on rural households’ livelihood: The case of Sodo FLR, South Central Ethiopia - Mister Abebe,; Mehari Alebachew,; Abdu Abdelkadir,; Degenet Abebaw,; Agena Anjulo,; Teshome Tesema,; Habtemariam Kassa, (International Journal of Agricultural Research, Innovation and Technology, 2024)
Ethiopia has pledged to restore 22 million ha of degraded and deforested lands by 2030. With the massive Forest Landscape Restoration (FLR) efforts underway, however, there are no sufficient empirical studies that signify the effectiveness of FLR in the country. Therefore, the study evaluated the impact of the FLR program on rural households’ livelihoods in Sodo, Southern Central Ethiopia. A two-stage random sampling technique was followed to draw the sample households, and 260 sample households (120 households from FLR participating and 140 households from non-FLR participating) were chosen randomly. Data on socio-demographic characteristics, head of household assets, access to credit, land size, household income and related expenditures were considered. In addition, data was gathered through key informant interviews, focus group discussions, direct field observations, and reviewing project documents and activity reports. The data was analyzed using descriptive statistics and Propensity Score Matching (PSM) technique. The results showed that FLR participants are likely to gain higher total and crop income than non-FLR participants. The average off-farm income of FLR participants also increased by 10252.4 ETB (200 USD). The number of beehives and the amount of honey produced was higher with FLR participants. FLR participants received more training and had better access to credit. Moreover, several households benefited from the FLR initiative's program offer to sustain their livelihoods by producing sheep and poultry. In conclusion, FLR initiatives should be combined with agricultural intensification and diversification as well as business-oriented forest development for better impact. Int. J. Agril. Res. Innov. Tech. 13(2): 14-21, Dec 2023